Economic consequences of better health: insights from clinical data - Ogbuoji, Osondu; Vollmer, Sebastian; Jamison, Dean T.; Bärnighausen, Till (The BMJ, 2020)
Osondu Ogbuoji and colleagues discuss the links between economic outcomes and health and how to improve our understanding of the effects of specific diseases
Gesehen am 27.10.2020